Cross-Sector Misallocation with Sector-Specific Distortions - Leal, Julio (Published by Oxford University Press on behalf of the World Bank, 2019)
In this paper, the author seeks to sharpen the understanding of the economic channels through which sector-specific distortions affect aggregate outcomes. Thea author pay special attention on how cross-sector misallocation might arrive as a result of these distortions, and clarify how models of resource misallocation across heterogeneous firms differ from models of resource misallocation across sectors. The author present facts that suggest the presence of such distortions in Mexico, a noteworthy developing country. The paper highlights the importance of understanding the origin and nature of sector-specific distortions for policy design.